Next-generation sequencing-based detection in a breast MMPMN patient with EGFR T790M mutation: a rare case report and literature review - Lv, Huiyun; Tian, Aijuan; Zhao, Shanshan; Zhao, Jinbo; Song, Chen (Frontiers in Oncology, 2023)
Multiple primary malignant neoplasms (MPMNs) are difficult to identify from the metastasis or recurrence of malignant tumors. Additionally, the genetic mutations in each primary tumor vary from each other; therefore, it is critical to explore potential abnormal genes. Next-generation sequencing (NGS) technology has emerged as a reliable approach for detecting mutated genes in primary tumors and can provide several targeted therapeutic options for patients with MPMNs. Here, we report a case of metachronous multiple primary malignant neoplasm (MMPMN) patient with primary ovarian and breast cancer. Targeted NGS genetic profiling revealed a rare EGFR T790M mutation in this patient’s primary breast tumor tissue, which has only been reported previously in breast cancer (BC). Based on the NGS results, osimertinib was recommended for this patient. Although this patient did not receive osimertinib because of gastrointestinal hemorrhage, this case highlights the significance of NGS technology in the diagnosis and treatment of MPMNs.